The Role Of Artificial Intelligence In Transforming Healthcare Leadership: A Systematic Review Of Current Trends And Future Directions (Journal of Namibian Studies : History Politics Culture, 2022)
Objective: This systematic review aims to comprehensively examine the role of artificial intelligence in reshaping healthcare leadership in Saudi Arabia. Methodology: A systematic search was conducted across databases such as PubMed and Google Scholar to identify pertinent studies published between 2018 to 2022. Articles meeting specific inclusion criteria, including English language and focused examination of artificial intelligence in healthcare leadership, were selected. Additionally, chosen articles were required to utilize established measurement scales and provide significant data on artificial intelligence's impact on healthcare leadership within organizational settings. Following initial screening and quality assessment, twelve studies were deemed suitable for synthesis. Findings: The analysis revealed a consistent association between artificial intelligence implementation and healthcare leadership dynamics. Artificial intelligence emerged as a beneficial factor in both mitigating challenges and fostering positive outcomes within healthcare leadership contexts. Conclusion: This review underscores the significance of artificial intelligence integration in healthcare leadership and administration. The research highlights the potential for artificial intelligence to effectively enhance and transform healthcare leadership practices, thereby shaping the future landscape of healthcare in Saudi Arabia.